Calculating landscape diversity with information-theory based indices: A GRASS GIS solution - Rocchini, Duccio; Delucchi, Luca; Bacaro, Giovanni; Cavallini, Paolo; Feilhauer, Hannes; Foody, Giles; He, Kate; Nagendra, Harini; Porta, Claudio; Ricotta, Carlo; Schmidtlein, Sebastian; Spano, Lucio Davide; et al. (Ecological Informatics, 2013)
The assessment of species diversity in relatively large areas has always been a challenging task for ecologists, mainly because of the intrinsic difficulty to judge the completeness of species lists and to undertake sufficient and appropriate sampling. Since the variability of remotely sensed signal is expected to be related to landscape diversity, it could be used as a good proxy of diversity at species level.It has been demonstrated that the relation between species and landscape diversity measured from remotely sensed data or land use maps varies with scale. However, Free and Open Source tools (allowing an access to the source code) for assessing landscape diversity at different spatial scales are still lacking today. In this paper, we aim at: i) providing a theoretical background of the mostly used diversity indices stemmed from information theory that are commonly applied to quantify landscape diversity from remotely sensed data and ii) proposing a free and robust Open Source tool (r.diversity) with its source code for calculating diversity indices (and allowing an easy potential implementation of new metrics by multiple contributors globally) at different spatial scales from remotely-sensed imagery or land use maps, running under the widely used Open Source program GRASS GIS.r.diversity can be a valuable tool for calculating landscape diversity in an Open Source space given the availability of multiple indices at multiple spatial scales with the possibility to create new indices directly reusing the code.We expect that the subject of this paper will stimulate discussions on the opportunities offered by Free and Open Source Software to calculate landscape diversity indices. © 2012 Elsevier B.V.
Keywords: Biodiversity; Diversity metrics; GRASS GIS; Landscape ecology; R.diversity; Spectral variability